1990
DOI: 10.1111/j.1432-1033.1990.tb19328.x
|View full text |Cite
|
Sign up to set email alerts
|

Two of the three genetic variants of goat αs1‐casein which are synthesized at a reduced level have an internal deletion possibly due to altered RNA splicing

Abstract: This paper describes the elucidation of the primary structure of the three genetic variants of goat asl-casein, asl-Cn D, E and F, which have been found to be associated with reduced amounts of asl-casein in milk. Variant E has the same electrophoretic mobility as variant B, but differs from the latter by the substitutions of Arg for Lys and of Thr for Ala at positions 100 and 195. A genetically controlled event which does not affect the amino acid sequence of this variant might be responsible for its lower ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 11 publications
1
41
0
4
Order By: Relevance
“…Studies performed on goat milk have reported extensive genetic polymorphism of a s1 -casein with at least 14 autosomal alleles at the goat a s1 -casein locus, distributed in seven different classes of protein variants associated with four levels of expression [34]. a s1 -Casein A, B, C and E variants differ from each other in amino acid substitutions, while a s1 -casein F and G variants, associated with a low level of protein synthesis, are internally deleted [14,60]. The establishment of the overall organisation of the goat a s1 -casein gene (Fig.…”
Section: Casual Exon-skippingmentioning
confidence: 99%
“…Studies performed on goat milk have reported extensive genetic polymorphism of a s1 -casein with at least 14 autosomal alleles at the goat a s1 -casein locus, distributed in seven different classes of protein variants associated with four levels of expression [34]. a s1 -Casein A, B, C and E variants differ from each other in amino acid substitutions, while a s1 -casein F and G variants, associated with a low level of protein synthesis, are internally deleted [14,60]. The establishment of the overall organisation of the goat a s1 -casein gene (Fig.…”
Section: Casual Exon-skippingmentioning
confidence: 99%
“…Le logiciel utilisé pour estimer les effets des allèles est le PEST (Groeneveld et Kovac, 1990 (Leroux et al, 1990Leroux, 1992 (Remeuf, 1993;Grosclaude et al, 1994;Vassal et al, 1994). Cet (Brignon et al, 1990;Leroux et al, 1992;Martin 1993;Grosclaude et al, 1994). Le …”
Section: Introductionunclassified
“…Le polymorphisme des caséines de chèvre a été dé-crit par les généticiens: pour le gène de la caséine a s 1' il existe au moins 7 variants génétiques, amenant à des taux de caséine différents (Boulanger et al, 1984 ;Brignon et al, 1990). De plus, la teneur en caséine totale du lait est en relation directe avec la teneur en caséine a s 1 (Leroux et al,1990).…”
Section: Introductionunclassified